GAMBARAN TINGKAT PENGETAHUAN PENGGUNAAN ANTIBIOTIK PADA MAHASISWA PROGRAM STUDI D3 MANAJEMEN INFORMATIKA DAN KOMPUTERISASI AKUNTANSI UNIVERSITAS IMELDA MEDAN - Samgryce Siagian, Hartika; Nasution, Dina Rahmadani; Samosir, Sri Rezeki (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Antibiotics are chemical compounds produced by a microorganism (especially produced by fungi) or produced synthetically which can be used to kill or inhibit the development of bacteria and other organisms. The use of antibiotics must be recommended by a doctor if the bacterial infection does not improve, the infection suffered is a contagious infection, and there is a risk of complications from the bacterial infection. Antibiotic resistance is a condition where bacteria become resistant to antibiotics. This occurs because the patient does not understand how to take antibiotics that have been recommended by the doctor. The aim of this research is to determine the level of knowledge of antibiotic use among students of the D3 Informatics Management and Computerized Accounting study program at Imelda University, Medan. The method used is a descriptive method using a questionnaire distributed to respondents. The sample is 50 active students from Informatics Management and Accounting Computerization Study Program. The sampling technique in this research uses the systematic Random Sampling method. Data analysis was carried out descriptively by displaying the percentage of knowledge level of 76-100% good knowledge level, 56-75% sufficient knowledge level and 0-56% poor knowledge level. The results of this research show that the description of the level of knowledge of students on the use of antibiotics in students of the third diploma study program in Informatics Management is better than Computerized Accounting, this is proven by the percentage of knowledge level of Informatics Management of 12 respondents (48%) in the sufficient category and the level of knowledge of Computerized Accounting as many as 11 respondents (44%) were in the poor category.